2013
DOI: 10.1200/jop.2012.000797
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Clinical Trial–Associated Workload in a Community Clinical Oncology Program

Abstract: Purpose: The ability to quantify clinical trial-associated workload can have a significant impact on the efficiency and success of a research organization. However, methods to effectively estimate the number of research staff needed for clinical trial recruitment, maintenance, compliance, and follow-up are lacking. To address this need, the Wichita Community Clinical Oncology Program (WCCOP) developed and implemented an acuitybased workload assessment tool to facilitate assessment and balancing of workload amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 8 publications
0
23
0
4
Order By: Relevance
“…In contrast to published experiences, however, we found that phase I and even non-therapeutic trials did not present an insurmountable barrier to accrual in community oncology practices. In a previous survey of 51 community practices, which included both federally sponsored and private non-academic affiliated practices, half of the practices self-reported that they did not accrue to phase I trials, 53% did not accrue to investigator-initiated trials, and 33% did not enroll on correlative science trials [ 11 ]. It is likely that many investigator-initiated trials and translational “non-therapeutic” trials can meet the needs of community oncology patients, and that academic-affiliated community sites are best poised to engage patients in accrual to these types of studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to published experiences, however, we found that phase I and even non-therapeutic trials did not present an insurmountable barrier to accrual in community oncology practices. In a previous survey of 51 community practices, which included both federally sponsored and private non-academic affiliated practices, half of the practices self-reported that they did not accrue to phase I trials, 53% did not accrue to investigator-initiated trials, and 33% did not enroll on correlative science trials [ 11 ]. It is likely that many investigator-initiated trials and translational “non-therapeutic” trials can meet the needs of community oncology patients, and that academic-affiliated community sites are best poised to engage patients in accrual to these types of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, one was a quality improvement study (Cusack et al, 2004a(Cusack et al, , 2000bJones et al, 2004) and two were expert opinion or commentary (Cassidy & Macfarlane, 1991;Smuck et al, 2011). In relation to psychometric assessments, eight had no reliability and validity data reported (Berridge et al, 2010;Ellis et al, 2012;Good et al, 2013;Gwede et al, 2000aGwede et al, , 2000bJames et al, 2011aJames et al, , 2011bMcCarthy, 1997;Roche et al, 2002;Smuck et al, 2011). Five studies mentioned reliability and validity but no data were presented (Briggs, 2008;Coffey et al, 2011;Cusack et al, 2004aCusack et al, , 2000bJones et al, 2004;Oddone et al, 1995;Penberthy et al, 2012).…”
Section: Acuity Tools Pertaining To Research Intensitymentioning
confidence: 99%
“…The Wichita Protocol Acuity Tool, which was used by a single oncology-focused research program for over 10 years, 1 was selected as the model on which the ASCO tool would be based. The Forum adapted this Wichita tool to create the ASCO Clinical Trial Workload Assessment Tool, which is designed to have widespread applicability among community-based research sites.…”
Section: Asco Clinical Trial Workload Assessment Toolmentioning
confidence: 99%